Armored catfish (Siluriformes: Loricariidae) from the Miocene of southern Pampas and its palaeobiogeographical implications - Bogan, Sergio (2019)
Armored catfishes are grouped within the clade Loricariidae. They are typically Brazilian freshwater fishes that show a high taxonomic diversity in South America and are distributed from Costa Rica to Buenos Aires province, Argentina. The aim of the present contribution is to describe an isolated pectoral spine of a loricariid coming from Late Miocene beds of southern Pampas, at Buenos Aires province, Argentina. This record constitutes the first finding of a fish in the Chasicó area, Arenas Blancas fossiliferous site, and is located far from the current geographical range of loricariids. The finding of a loricariid is congruent with the idea of a warm climate and the possibility that southern paleobasins of Pampas and northern Patagonia were hydrographically connected with paleobasins that hold Brazilian freshwater fishes.